Les « tracteurs du président » au Tchad : machines agricoles ou instrument politique ? - Ronan Mugelé (EchoGéo)
At the end of the 2000s, the Chadian State implemented an ambitious policy of modernization and development of agriculture. In particular, it sought to encourage the mechanisation and motorisation of peasant work through the dissemination of agricultural tractors through the TEAM programme, a technical partnership formalised with India. This article describes and analyses the conditions of introduction and use of these tractors. It shows how the material and technical dimension of the machine is deeply linked to its immaterial and symbolic component, and how this articulation redefines its uses.